1997
DOI: 10.1515/cclm.1997.35.2.85
|View full text |Cite
|
Sign up to set email alerts
|

Evolution of Haptoglobin Concentration in Serum during the Early Phase of Acute Myocardial Infarction

Abstract: is a haemoglobin-binding acute phase protein with three genetic types: Hp 1-1, Hp 2-1, Hp 2-2. We investigated 45 patients during the first 48 hours of acute myocardial infarction, and studied determinant factors and clinical correlates. Upon hospital admission, serum haptoglobin concentration was increased (1.95 ± 0.94 g/1, mean ± SD, P < 0.001) versus the reference population (0.97 ± 0.46 g/l, n = 107), independent of haptoglobin type: 1.84 ± 0.64 g/1 (Hp 1-1, n = 11) (P < 0.01), 1.98 ± 0.79 g/l (Hp 2-1, n =… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
9
0

Year Published

1997
1997
2017
2017

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 20 publications
0
9
0
Order By: Relevance
“…Hemoglobin is a potent oxidant that is released from red cells because of hemolysis in the setting of IR and MI (21). We have proposed that the anti-oxidant and antiinflammatory functions of Hp may be attributed to its interaction with Hb.…”
Section: Discussionmentioning
confidence: 99%
“…Hemoglobin is a potent oxidant that is released from red cells because of hemolysis in the setting of IR and MI (21). We have proposed that the anti-oxidant and antiinflammatory functions of Hp may be attributed to its interaction with Hb.…”
Section: Discussionmentioning
confidence: 99%
“…We found that there was no increase in IL-10 in Hp 2 mice after one hour of reperfusion in this model but there was a 3-4 fold significant increase in IL-10 in the serum of the Hp 1 mice at one hour after the onset of reperfusion. While we have no direct proof that this process is mediated via Hp-Hb and CD163, hemolysis is known to occur rapidly after ischemia-reperfusion as demonstrated by an acute fall in Hp concentrations [76]. [19] Kumamoto, M., Nakashima, Y. and Sueishi, K. …”
Section: Discussionmentioning
confidence: 99%
“…We have recently described simple procedures, in which each Hp phenotype can be isolated using a monoclonal antibody (mAb) affinity column [11,12]. Limited studies [13][14][15] have indicated that the plasma concentration of Hp 1-1 is differentially higher than that of 2-1 and 2-2, but other reports are varied and inconsistent [16][17][18][19]. In the present study, we hypothesized that the inconsistency of reported Hp values could be due to the differences in surface antigenic structures among Hp 1-1, 2-1, and 2-2.…”
Section: Introductionmentioning
confidence: 99%